α-IMINOCARBENOS METÁLICOS DERIVADOS DE N-SULFONIL-1,2,3-TRIAZÓIS NA SÍNTESE DE ALCALOIDES - Vinícius V. Souza; Cristiano Raminelli (Química Nova)
The study of carbenes and metal carbenes has attracted researchers from different countries due to the versatility of these reactive species in preparative organic chemistry. In this review, we discuss the structural aspects, reactivity, and formation methods of carbenes, which provide theoretical support for understanding the structure/reactivity relationship of metal carbenes, whose classifications and formation methods have been presented. Emphasis is placed on the class of α-imino metal carbenes, which have allowed the construction of various heterocyclic compounds, including alkaloids with complex structures. Total and formal syntheses of nitrogen-containing compounds using α-imino metal carbenes from N-sulfonyl-1,2,3-triazoles have been reviewed. In this regard, an overview of the synthetic routes established in these works, including the key reactions highlighted by the authors, has been provided.